-34=11(k-2)-5k

Simple and best practice solution for -34=11(k-2)-5k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=11(k-2)-5k equation:



-34=11(k-2)-5k
We move all terms to the left:
-34-(11(k-2)-5k)=0
We calculate terms in parentheses: -(11(k-2)-5k), so:
11(k-2)-5k
We add all the numbers together, and all the variables
-5k+11(k-2)
We multiply parentheses
-5k+11k-22
We add all the numbers together, and all the variables
6k-22
Back to the equation:
-(6k-22)
We get rid of parentheses
-6k+22-34=0
We add all the numbers together, and all the variables
-6k-12=0
We move all terms containing k to the left, all other terms to the right
-6k=12
k=12/-6
k=-2

See similar equations:

| 181=-y+278 | | n+7+8n=-2 | | 8h-20=h+15 | | 11+v/5=18 | | 38+9+x=180 | | 9(2-t)+5=68 | | 18=-x-8x | | b/14+362=389 | | 5n-7n=-14 | | 18=6p-4.5p+12 | | h+4=19-2h | | 6n-70+2n+10=180 | | 20y+5-5y=65 | | x=0.6.40= | | -2=4m-5m | | 5x-9x+3=11 | | 6+b=2 | | 7z-3=5z+11 | | 3(x+3)=153 | | 3h-2=h+10 | | 3n=5−2n | | -3n=5−2n | | 6s=-s+7 | | 9=-10+w/4 | | 3y=27.25 | | 5x+3(9.08)=39 | | n-7=-30 | | -3/10=-3/5+z | | 5x-5-32=x-5 | | A^-7a-3a=0 | | 10=5/2w | | 165=10x |

Equations solver categories